Trends in Pediatric Malignancy Cases at a Tertiary Care Center in Bihar, India: A Retrospective Study - Singh, Dharmendra; Singh, Pritanjali; Mandal, Avik; Mondal, Himel (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: Pediatric malignancies constitute a significant proportion of cancer cases in India, and yet, there is a dearth of information on the distribution of these cancers in the state of Bihar. To address this knowledge gap, we conducted this study to analyze the pattern of pediatric malignancies. Materials and Methods: This cross-sectional observational study was conducted in a tertiary care hospital in eastern India. The study was carried out at the Department of Radiotherapy, where we enrolled patients between the ages of 0-18 years who were referred to our department. Results: We analyzed the data of 306 patients, of which 22 (7.19%) were diagnosed with benign tumors, and 284 were diagnosed with malignancies. Among the 284 patients with malignancies, 208 (73.24%) had solid tumors, and 76 (26.76%) had hematological malignancies. The most common hematological malignancy was acute lymphoblastic leukemia (32.89%), followed by Hodgkin lymphoma (30.27%) and non-Hodgkin lymphoma (27.63%). Among solid malignancies, sarcoma was the most prevalent (31.25%), followed by germ cell tumors (17.79%), and Wilms’ tumor (16.83%). Conclusion: We analyzed the data of 306 patients, of whom 22 (7.19%) were diagnosed with benign tumors, and 284 were diagnosed with malignancies. Among 284 patients with malignancies, 208 (73.24%) had solid tumors, and 76 (26.76%) had hematological malignancies. The most common hematological malignancy was acute lymphoblastic leukemia (32.89%), followed by Hodgkin lymphoma (30.27%) and non-Hodgkin lymphoma (27.63%). Among solid malignancies, sarcoma was the most prevalent (31.25%), followed by germ cell tumors (17.79%), and Wilms’ tumor (16.83%).